Band nonparabolicity effect on spectral properties of quantum ring. (March 2017) - García, L.F.; Revinova, S.Yu.; Mikhailov, I.D.
Abstract: We study the effect of the non-parabolicity of the conduction band and of the interband mixing, on the Aharonov Bohm oscillations of the energy levels of a volcano-shaped thin layer, made of InAs material and deposited on the GaAs substrate, by using the Kane model. We derive a simple interpolative relationship between geometrical parameters of the layer and the confinement potential governing the in-plane electron's movement, which allows us to separate the non-linear energy confinement problem in a volcano-shaped structure with a special geometry. Our results show that the nonparabolicity of dispersion of the conduction band, given by the Kane formula, conduces to a significant lowering of the charge carriers' energies and their stronger localization inside the ring. On the contrary, the nonparabolicity almost does not change neither the amplitude nor the period of the Aharonov Bohm oscillations. Additionally, we analyze the interplay between the localization and tunneling of the charge carriers, generated by the external magnetic field in structures with radially directed single, double and quadruple valleys. Highlights: The effect of the non-parabolicity of the conduction band in volcano-shaped InAs/GaAs nanostructure has been studied by using the Kane model. A significant lowering of the electron energy in comparison with one-band effective mass approximation has been found. The influence of radially directed single, double and quadruple valleys on the Aharonov Bohm oscillations bands has been considered.